ASSOCIATION BETWEEN HYPOXIC INDUCIBLE FACTOR (HIF) -1 ALPHA WITH HISTOPATHOLOGICAL FEATURES OF GASTRITIS - Azmi Zulfa Hidayati & Gontar Alamsyah Siregar (International Journal of Research Science and Management, 2020)
Background: The incidence of gastritis in Southeast Asia is around 583,635 of the total population each year. There are several features of histopathology of gastritis, namely chronic inflammation, acute inflammation, gastric mucosal atrophy, and metaplasia. The association between inflammation and hypoxia has been found since many years ago. Hypoxic Inducible Factor (HIF) is activated in response to hypoxia and inflammation. . In hypoxic conditions, there will be an increase in the production of HIF-1α. This study was conducted to determine the relationship of HIF-1α expression with gastritis degree, so that it can be known whether HIF-1α can be used as a parameter of the degree of gastric mucosa damage. Methods: The design of this study was a cross-sectional study with independent variables such as histopathological severity of gastritis (degree of lymphocyte infiltration, degree of neutrophil activity, degree of atrophy, and degree of intestinal metaplasia) and the dependent variable was serum HIF-1α levels. This study was conducted at the Endoscopic Unit of H. Adam Malik GeneralHospital in Medan. Statistical analysis was carried out with the SPSS (version 22.0). Results: HIF-1α levels are higher in moderate + severe lymphocyte infiltration than normal + mild degrees. HIF levels are higher in moderate + severe neutrophil activity than normal + mild degrees. HIF-1α levels are higher in moderate + severe atrophy than normal + mild degrees. HIF-1α levels are higher in mild metaplasia degrees than without metaplasia. Conclusions: Significant association was found between histopathological features of gastrits and serum HIF1α levels..